Contributing Factors and Outcome after Cryotherapy of Molluscum Contagiosum among Patients Attending Tertiary Hospital, Northern Tanzania: A Descriptive Prospective Cohort Study - Peter J. Chapa; Daudi R. Mavura; Rune Philemon; Lulyritha Kini; Elisante J. Masenga (Dermatology Research and Practice)
Background. Molluscum contagiosum (MC) is a benign infection caused by a member of the Poxviridae family, molluscum contagiosum virus (MCV). The contributing factors for MCV infection are different in different populations and study areas. Few studies have been conducted to determine the effectiveness of cryotherapy in the treatment of MC. The study’s objectives were to determine contributing factors and outcome after cryotherapy of MC among patients attending a tertiary hospital in Northern Tanzania. Methods. A hospital-based cohort study was conducted at the Regional Dermatology Training Centre (RDTC) from September 2018 to August 2019, involving all patients clinically diagnosed with MC. We used a consecutive sampling method to recruit study participants. We treated all participants with cryotherapy and assessed them after two weeks. Data were collected using a structured questionnaire and analyzed using Statistical Package for the Social Sciences (SPSS) software version 21. Results. There were 49 patients with MC who agreed to participate in this study with a median age of 8 (IQR 3–22). We found 18.4% of patients with active atopic dermatitis (AD) had MC while those with a history of atopic diseases (Ad) were 32%, and 22.4% had a history of using immunosuppressive drugs. The clearance rate of cryotherapy on MC lesions was found to be 94%. Hypopigmentation was the commonest adverse effect. Conclusion. The findings of this study show that AD and immunosuppression may be contributing to MC development. Based on the clearance rate results, cryotherapy has shown to be effective and may be used in the treatment of MC.